Highly efficient surface functionalization for janus carbon nanofluid large-scale synthesis

CN122996150APending Publication Date: 2026-10-27SAUDI ARABIAN OIL CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580022832.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-14
Filing Date
2025-03-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,多种约束因素会影响现有纳米流体的流体-流体相互作用和流体-岩石相互作用以及随后的原油采收

Benefits of technology

[0008]图1是根据本公开的一个或多个实施例的方法的框式流程图。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996150A_ABST
    Figure CN122996150A_ABST
Patent Text Reader

Abstract

A method of making an enhanced oil recovery composition is provided. The method includes carbonizing (200) a waste carbon material (202) to provide carbon particulates (208) having a hydrophobic surface (404); functionalizing (300) the carbon particulates (208) with a basic solution (302) such that the carbon particulates (208) have a hydrophilic surface (306); and milling (400) the carbon particulates (208) to provide carbon nanoparticles (406). The carbon nanoparticles (406) have a hydrophilic surface (306) and a hydrophobic surface (404). The method can further include mixing the carbon nanoparticles with a water-based fluid to provide an enhanced oil recovery fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Background Technology

[0001] Among the major challenges facing the modern world, meeting energy demands and protecting the environment are two of the top priorities. Conventional fossil fuels remain the primary energy source in addressing our ever-increasing energy needs; however, extracting these fuels from mature oil fields is becoming increasingly difficult. Recent advances in petroleum engineering research have demonstrated that nanomaterials can be used in oilfield waterflooding techniques (often referred to as nanofluid displacement) to improve crude oil displacement. One advantage of nanofluids stems from the small size of the nanomaterials they contain, which can alter the wettability of reservoir rocks and / or change the interfacial tension (IFT) at the water-oil interface, thereby enhancing oil recovery. However, several constraints affect the fluid-fluid and fluid-rock interactions of existing nanofluids and subsequent oil recovery.

[0002] Similarly, although environmental protection is a long-term goal, plastic waste and biomass waste, as the two most abundant types of waste in the modern world, are highly durable and difficult to degrade. Therefore, developing efficient waste reuse and recycling strategies has become a major objective for various industries. Summary of the Invention

[0003] The present invention is provided to introduce some concepts that will be further described in the detailed embodiments below. The present invention is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an auxiliary basis for limiting the scope of the claimed subject matter.

[0004] In one aspect, the embodiments disclosed herein relate to a method for preparing an enhanced oil recovery composition. The method includes: carbonizing waste carbon material to provide carbon microparticles having a hydrophobic surface; functionalizing the carbon microparticles with an alkaline solution such that the carbon microparticles include a hydrophilic surface; and milling the carbon microparticles to provide carbon nanoparticles, wherein the carbon nanoparticles include both hydrophilic and hydrophobic surfaces. The method may further include mixing the carbon nanoparticles with an aqueous fluid to provide an enhanced oil recovery fluid.

[0005] In another aspect, the embodiments disclosed herein relate to an enhanced oil recovery method. The method includes: introducing an enhanced oil recovery composition into a hydrocarbon-bearing formation; displacing hydrocarbons from the hydrocarbon-bearing formation; and recovering the hydrocarbons. The enhanced oil recovery fluid comprises carbon nanoparticles having both hydrophilic and hydrophobic surfaces.

[0006] Other aspects and advantages of the claimed subject matter will be apparent from the following description and appended claims.

[0007] Brief description of the attached figures

[0008] Figure 1This is a block flowchart of a method according to one or more embodiments of the present disclosure.

[0009] Figure 2 This is a schematic diagram of the carbonization of waste carbon materials according to one or more embodiments of this disclosure.

[0010] Figure 3 This is a schematic diagram of carbon microparticle functionalization according to one or more embodiments of the present disclosure.

[0011] Figure 4 This is a schematic diagram of carbon nanoparticles before and after grinding according to one or more embodiments of the present disclosure.

[0012] Figure 5 This is a schematic diagram of a well environment according to one or more embodiments of the present disclosure.

[0013] Figure 6 This is a block flowchart of a method according to one or more embodiments of the present disclosure.

[0014] Figure 7 shows images of carbon particles prepared from lignin powder and dispersed in a hexane-water mixture: (a) unfunctionalized carbon microparticles, (b) functionalized carbon microparticles, and (c) milled Janus carbon nanoparticles.

[0015] Figure 8 shows images of carbon particles obtained from waste coffee powder and dispersed in toluene-water: (a) unfunctionalized carbon microparticles, (b) functionalized carbon microparticles, and (c) ground Janus carbon nanoparticles.

[0016] Figure 9 Raman spectral data of untreated particles and KOH-treated particles are shown. Detailed Implementation

[0017] Recent advances in enhanced oil recovery (EOR) technology have demonstrated that the effective use of nanotechnology in EOR fluids can enhance oil recovery. Generally, nanomaterials in EOR fluids can withstand the high temperatures and pressures of subsurface reservoirs and exhibit different surface properties compared to organic molecules in porous media such as reservoir rocks, thereby enabling access to crude oil that conventional surfactants and polymers used in EOR processes cannot reach. Depending on the specific physical characteristics and properties of the given nanomaterials, other benefits of using this technology may include: the ability to alter mineral wettability, the ability to reduce interfacial tension (IFT) at the oil-water interface, the ability to alter fluid viscosity, and / or the ability to generate structural separation pressures at the oil / rock interface.

[0018] Specifically, Janus nanomaterials with two or more different chemical or physical properties on their surface combine nanoparticle properties with surfactant-like properties. Therefore, developing economical and sustainable methods to produce the quantities of low-cost nanomaterials required for oilfield applications would be highly beneficial.

[0019] Carbon-containing waste (such as plastics) is ubiquitous in modern society. Plastics are made from a variety of synthetic polymer materials that typically degrade very slowly. Because most polymers are formed by chains primarily containing carbon atoms, this makes them excellent precursors for carbon materials such as carbon nanoparticles. Biomass waste is also considered a form of waste carbon. Biomass waste is a natural organic carbon source, primarily composed of organic macromolecules such as cellulose, hemicellulose, lignin, polysaccharides, and proteins. Currently, most biomass waste is discarded, landfilled, or openly burned, leading not only to resource waste but also potential environmental problems. Because biomass waste is renewable, environmentally friendly, and abundant, it can be used as a harmless carbon source for the production of carbon nanoparticles.

[0020] Because EOR nanofluids exhibit improved oil recovery compared to conventional fluids, carbon nanoparticles derived from waste carbon materials such as waste plastics or biomass waste can be used in EOR compositions and methods. Janus-structured carbon nanoparticles can provide further advantages as EOR nanoparticles. Such compositions and methods will help address two major challenges in the modern world: ever-increasing energy demands and environmental protection. Therefore, this invention relates to a method for preparing carbon nanoparticles from waste carbon materials, and EOR compositions and methods using such carbon nanoparticles.

[0021] Method for preparing EOR compositions

[0022] In one aspect, the embodiments disclosed herein relate to a method for preparing an EOR composition comprising Janus carbon nanoparticles. Specifically, the Janus carbon nanoparticles can be prepared from waste carbon materials, and therefore, the method can also serve as a method for reusing waste carbon materials. The method may include: carbonizing the waste carbon materials to form hydrophobic carbon microparticles; functionalizing the carbon microparticles to produce a hydrophilic surface; and milling the carbon microparticles to provide Janus carbon nanoparticles having asymmetric amphiphilic surface properties.

[0023] Figure 1 A method 100 for preparing an EOR composition comprising Janus carbon nanoparticles according to one or more embodiments is shown, and Figure 2 , Figure 3 and Figure 4The method is further described below. First, method 100 includes, at block 110, carbonizing the waste carbon material by a pyrolysis process to provide carbon microparticles. As used herein, “carbonization” refers to the process in which carbon-containing material (such as the aforementioned waste carbon material) is converted or “carbonized” into a material, or converted into a material primarily composed of amorphous carbon, at high temperature under an inert atmosphere. The waste carbon material can be any carbon-containing waste plastic material or biomass waste. The carbon can be present in hydrocarbons, aromatic rings, and combinations thereof.

[0024] Suitable waste plastic materials that can be carbonized include polymers such as polypropylene (PP), polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), polyethylene terephthalate (PET), polyester (PES), polyamide (PA), polyvinyl chloride (PVC), polyurethane (PU), polycarbonate (PC), polyvinylidene chloride (PVDC), polyethylene (PE), and combinations thereof. In some embodiments, the waste plastic material includes PET, PP, PVC, PS, high-density polyethylene (HDPE), or low-density polyethylene (LDPE). The waste plastic material can be post-consumer waste plastic material, such as plastic water bottles.

[0025] Suitable biomass wastes that can be carbonized include seaweed, algae, coffee, tea leaves, fruit peels, nut shells, flour, grains, straw, straw, eggs, milk, vegetable oil, animal meat, and combinations thereof. In a particular embodiment, the biomass waste contains starch, chitin, lignin, cellulose, triglycerides, fatty acids, and combinations thereof.

[0026] In one or more embodiments, the waste carbon material is processed prior to carbonization. The waste plastic material can be processed by cutting, grinding, or cryogenic grinding to provide plastic fragments. In embodiments employing cryogenic grinding, a suitable grinder (e.g., a SPEX SamplePrep 6775 cryogenic grinder) can be used to grind a sample cooled with liquid nitrogen (N2) at a suitable grinding rate (e.g., 10 times per second (cps)). The waste plastic material can be processed into plastic fragments of suitable size. For example, in one or more embodiments, the plastic fragments have suitable sizes ranging from millimeters to sub-millimeters, such as 1×1×1 mm, 0.5×0.5×5 mm, or 0.1×0.1×0.1 mm, etc. The biomass waste can be processed to provide dried biomass waste flakes with a size equal to or less than one millimeter. In some embodiments, the biomass waste can be a dry powder. The biomass waste can be processed by any method known in the art.

[0027] According to one or more embodiments, Figure 2An exemplary carbonization process 200 is depicted. The carbonization of waste carbon materials can be carried out according to any method known in the art. For example, such as... Figure 2 As shown, the carbonization 200 of waste carbon material 202 can be carried out in crucible 204. The waste carbon material 202 can be carbonized in a furnace, such as... Figure 2 As indicated by arrow 206. In one or more embodiments, the waste carbon material is carbonized by heating it to an elevated temperature and maintaining it for a period of time in an inert atmosphere such as nitrogen (N2) or argon (Ar) or in a vacuum. During carbonization, the elevated temperature can be in the range of 300 to 550°C. For example, in one or more embodiments, the waste carbon material is carbonized at an elevated temperature that is in the range of a lower limit selected from one of 300, 325, 350, 375, 400, and 425°C to an upper limit selected from one of 425, 450, 475, 500, 525, and 550°C, wherein any lower limit can be paired with any mathematically compatible upper limit.

[0028] As described above, the waste carbon material can be heated at the elevated temperature for a period of time to achieve carbonization. In one or more embodiments, the waste carbon material can be heated for approximately 15 to approximately 60 minutes. For example, the carbonization of the waste carbon material can be sustained for a time ranging from a lower limit selected from one of 15, 20, 35, 30, and 35 minutes to an upper limit selected from one of 40, 45, 50, 55, and 60 minutes, wherein any lower limit can be paired with any mathematically compatible upper limit.

[0029] Carbonization 200 produces amorphous carbon particles 208. The carbonization of the waste carbon material can be confirmed using analytical methods known in the art. Specifically, methods including Raman spectroscopy, etc., can be used. 1 H NMR spectroscopy, 13 Spectroscopic methods, including C NMR spectroscopy, scanning electron microscopy (SEM) equipped with energy-dispersive X-ray spectroscopy (EDS), and infrared (IR) spectroscopy, are used to characterize carbonized waste and confirm its chemical structure.

[0030] The carbonized waste can be further processed to provide powder. In one or more embodiments, after carbonization 200, the powder is provided by grinding in an agate mortar or ball mill, or by other grinding methods known in the art. In embodiments using ball milling, the dry carbon powder can be ground for 30 to 120 minutes at a suitable frequency (e.g., 35 Hz) in a suitable ball mill (e.g., a Retsch IM 500 nanometer mill). The powder may comprise particles with an average particle size in the micrometer (μm) range. Therefore, the powder may also be referred to herein as “carbon microparticles”.

[0031] The carbon microparticles 208 disclosed herein may have an average particle size of about 5.0 to about 500 μm. The particle size can be measured by scanning electron microscopy (SEM), transmission electron microscopy (TEM), or dynamic light scattering (DLS). In one or more embodiments, the carbon microparticles 208 may have an average particle size ranging from a lower limit selected from 5.0, 10, 50, 100, 150, 200, and 250 μm to an upper limit selected from 250, 300, 350, 400, 450, and 500 μm, wherein any lower limit can be paired with any mathematically compatible upper limit. In a particular embodiment, the carbon microparticles 208 have an average particle size of about 10 μm.

[0032] The carbon microparticles 208 disclosed in this paper can have a size of 2 to 50 μm. 2 The average specific surface area is per g. Specific surface area can be measured using any method known in the art. In one or more embodiments, the specific surface area is measured using the Brunauer-Emmett-Teller (BET) surface analysis technique. The carbon microparticles 208 disclosed herein may have a hydrophobic surface.

[0033] Method 100 includes, at frame 120, functionalizing the carbon microparticles with an alkaline solution. Figure 3 An exemplary embodiment of functionalization 300 is depicted. The carbon microparticles can be functionalized to provide hydrophilic functional groups on the surface of the microparticles. Such a hydrophilic surface 306 can exhibit strong hydrogen bonding capabilities. Suitable functional groups for the hydrophilic surface 306 include hydroxyl groups.

[0034] Functionalization 300 of the carbon microparticles 208 may include contacting the carbon microparticles with an alkaline solution 302. In one or more embodiments, the alkaline solution 302 is a potassium hydroxide (KOH) solution. The solvent of the alkaline solution may be a 1:1 mixture of water and ethanol by volume. In one or more embodiments, the solvent (water to ethanol) ratio may be 1:9, 2:8, 3:7, 4:6, or 6:4, 7:3, 8:2, and 9:1. In one or more embodiments, the concentration of the alkaline solution is in the range of 1.0 to 4.0 M.

[0035] During contact with the alkaline solution, the carbon microparticles 208 can be sonicated for a period of time using a probe-type sonicator 304. The sonication time can range from 1 to 15 minutes. In one or more specific embodiments, the probe-type sonicator (e.g., Fisher Scientific, CL-18 model) can operate at 120 watts and 20 kHz.

[0036] After ultrasonic treatment, carbon particles 208 can be separated from alkaline solution 302 as indicated by arrow 308 and dried at 100°C. After drying, the carbon particles are heated in a furnace as indicated by arrow 310, as previously described regarding the carbonization of waste carbon materials. The second carbonization can be carried out at a temperature ranging from a lower limit selected from one of 300, 325, 350, 375, 400, and 425°C to an upper limit selected from one of 425, 450, 475, 500, 525, and 550°C, wherein any lower limit can be paired with any mathematically compatible upper limit. The second carbonization can be carried out for a time ranging from a lower limit selected from one of 15, 20, 35, 30, and 35 minutes to an upper limit selected from one of 40, 45, 50, 55, and 60 minutes, wherein any lower limit can be paired with any mathematically compatible upper limit. In one or more embodiments, heating produces functionalized carbon microparticles having a hydrophilic surface 306.

[0037] After surface functionalization, the previously hydrophobic carbon particles are well dispersed in water, indicating that the carbon surface has been uniformly hydrophilically functionalized. The functionalized carbon surface can be confirmed using analytical methods known in the art. Specifically, the functionalized carbon particles can be characterized using FTIR spectroscopy and compared with the original carbon particles. In other embodiments, Langmuir isotherms, such as surface pressure-surface area curves or π-A curves, can be measured at the water / air interface using a Langmuir bath.

[0038] Method 100 also includes grinding functionalized carbon microparticles at frame 130. Figure 4 An exemplary embodiment of a grinding process 400 is depicted. For example, the grinding process 400 may be performed using a ball mill. In one or more specific embodiments, the ball mill may be a Netzsch MiniCer for wet samples and having 0.5 mm grinding beads. The mixture to be ground in the ball mill may include a lubricant. The lubricant may include glycols, ethanol, water, and combinations thereof. The ball mill may also include grinding media. The grinding media may include zirconium oxide, tungsten carbide, silicon carbide, alumina, steel balls, and combinations thereof. The grinding media may have a diameter larger than the average diameter of the functionalized carbon particles. For example, the particles of the grinding media may have a diameter on the sub-millimeter or micrometer scale.

[0039] Carbon microparticles 208 having a hydrophilic surface 306 can be ground into smaller particles by a grinding process 402 (such as ball milling described above). Ball milling 402 can be performed for a time ranging from 0.5 to 8 hours. In one or more embodiments, the functionalized carbon microparticles are ground for a time ranging from a lower limit selected from one of 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4.0 hours to an upper limit selected from one of 4.5 and 5.0 hours, wherein any lower limit can be paired with any mathematically compatible upper limit.

[0040] The ball mill 402 can be used at a grinding speed in the range of 2000 to 4000 rpm. In one or more embodiments, the grinding speed can be in the range of a lower limit selected from one of 2000, 2200, 2400, 2600, 2800 and 3000 rpm to an upper limit selected from one of 3000, 3200, 3400, 3600, 3800 and 4000 rpm, wherein any lower limit can be paired with any mathematically compatible upper limit.

[0041] As described above, milling functionalized carbon microparticles 400 provides carbon nanoparticles 406. Specifically, carbon nanoparticles 406 are produced by breaking the functionalized carbon microparticles into smaller nanoscale particles with asymmetric surface functionalization, namely Janus carbon nanoparticles. Since the Janus carbon nanoparticles are fragments of functionalized carbon microparticles, they may have a hydrophilic surface 306 derived from the hydrophilic surface of the functionalized carbon microparticles, and a hydrophobic surface 404 derived from the core of the carbon microparticles 208, which is composed of amorphous carbon. Therefore, ball milling 402 can produce carbon nanoparticles 406 that possess both a hydrophilic surface 306 and a hydrophobic surface 404. In one or more embodiments, the hydrophilic surface 306 of the carbon nanoparticles includes the same hydrophilic functional groups as those of the functionalized carbon microparticles. On the other hand, the hydrophobic surface 404 of the carbon nanoparticles 406 may be primarily composed of carbon.

[0042] In one or more embodiments, as measured by scanning electron microscopy (SEM), the Janus carbon nanoparticles 406 have an average particle size in the range of about 10 to 2000 nm. The carbon nanoparticles 406 prepared according to the disclosed method may have an average particle size in the range of a lower limit selected from one of 10, 50, 100, and 500 nm to an upper limit selected from one of 600, 1000, 1500, and 2000 nm, wherein any lower limit can be paired with any mathematically compatible upper limit. The carbon nanoparticles 406 disclosed herein may have a particle size of 10 to 500 nm. 2 / g average specific surface area.

[0043] As described above, the Janus carbon nanoparticles according to this disclosure have both hydrophilic and hydrophobic surfaces. Therefore, the disclosed Janus carbon nanoparticles can possess unique properties, such as surfactant-like surface properties. For example, when characterized according to the Langmuir isotherm, the carbon nanoparticles of the present invention can exhibit adsorption similar to conventional surfactants. Surfactants are widely used to enhance oil recovery due to their combined hydrophobic and hydrophilic properties. Therefore, incorporating the Janus carbon nanoparticles of one or more embodiments into an EOR fluid composition can benefit the EOR process.

[0044] The embodiments disclosed herein also relate to an EOR composition. The composition may include nanomaterials and a water-based fluid. In one or more embodiments, the nanomaterials in the EOR composition are the aforementioned carbon nanoparticles.

[0045] Based on the total weight of the EOR composition, the EOR composition may include Janus carbon nanoparticles ranging from about 0.001 wt% to about 3.0 wt%. For example, in one or more embodiments, the Janus carbon nanoparticles are present in the EOR nanofluid in an amount ranging from a lower limit selected from one of 0.001, 0.005, 0.01, 0.05, and 0.1 wt% to an upper limit selected from one of 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 wt%, wherein any lower limit may be paired with any mathematically compatible upper limit.

[0046] In one or more embodiments, the EOR composition comprises a water-based fluid. The water-based fluid comprises water. The water can be distilled water, deionized water, tap water, fresh water from surface or underground sources, produced water, formation water, natural and synthetic brine, brackish water, natural and synthetic seawater, black water, brown water, grey water, blue water, drinking water, non-drinking water, other water, and combinations thereof, suitable for wellbore environments. In one or more embodiments, the water used may naturally contain contaminants such as salts, ions, minerals, organic matter, and combinations thereof, provided that the contaminants do not interfere with the operation of the drilling fluid.

[0047] In one or more embodiments, the EOR composition comprises water ranging from about 97% to 99.9% by weight, based on the total weight of the EOR composition. In one or more embodiments, the water used for the EOR composition may have higher levels of salt or ions than fresh water, such as naturally occurring salts or ions in formation water, produced water, seawater, and brine. Without being bound by any particular mechanism or theory, increasing the water's saturation by increasing the concentration of salts or other organic compounds in the water can increase the density of the water, and consequently, the density of the EOR composition. Suitable salts may include, but are not limited to, alkali metal halides, such as chlorides, hydroxides, or carboxylates. In one or more embodiments, the salts included as part of the water-based fluid may include salts that dissociate into the following ions: sodium, calcium, cesium, zinc, aluminum, magnesium, potassium, iron, copper, strontium, silicon, lithium, chloride, bromide, carbonate, iodide, chlorate, bromate, formate, nitrate, sulfate, phosphate, hydroxide, and fluoride, and combinations thereof.

[0048] In one or more embodiments, the EOR composition comprises one or more salts with a total dissolved solids (TDS) in the range of about 0 to about 225,000 ppm (parts per million). For example, the EOR composition may contain one or more salts in an amount ranging from the lower limit of any one of 0, 5,000, 10,000, 20,000, 30,000, 50,000, 75,000, 100,000, and 125,000 ppm to the upper limit of any one of 125,000, 150,000, 175,000, 200,000, and 225,000 ppm, wherein any lower limit may be used in combination with any mathematically compatible upper limit.

[0049] In one or more embodiments, the EOR composition includes one or more additives. Any additives known in the art for use in EOR compositions may be used. Examples of such additives include, but are not limited to, surfactants, polymers, stabilizers, and / or mixtures thereof. In one or more embodiments, the additive may be included in the EOR composition in an amount of 0 to about 3% by weight, based on the total weight of the EOR composition.

[0050] In one or more embodiments, the EOR nanofluid can be characterized based on a variety of properties, such as viscosity, density, and uniformity. Furthermore, the presence of carbon nanoparticles in the fluid can lead to a reduction in the interfacial tension between the EOR fluid and the crude oil within the reservoir.

[0051] Enhanced oil recovery methods

[0052] In another aspect, embodiments of this disclosure relate to an enhanced oil recovery method using the above-described enhanced oil recovery composition. The method may include: introducing the enhanced oil recovery composition into a hydrocarbon-bearing formation; displacing hydrocarbons from the hydrocarbon-bearing formation; and recovering the hydrocarbons.

[0053] Figure 5 A well environment 500 according to one or more embodiments is depicted. The well environment 500 includes a subsurface region 510. The depicted subsurface region 510 has a wellbore wall 511 extending downward from the surface 505 into the subsurface region 510 and defining a wellbore 520. The subsurface region 510 also includes a target formation 550 to be treated. The target formation 550 has a target formation surface 555 that passes through the wellbore wall 511 to provide fluid communication between the target formation 550 and the wellbore 520. In this configuration, casing 512 and coiled tubing 513 extend downward through the wellbore 520 into the subsurface region 510 and toward the target formation 550. Figure 5 The structure allows the previously described embodiment, which includes an enhanced oil recovery composition, to be introduced into the underground region 510 and toward the target formation 550 via a pump 517 through a continuous tubing 513.

[0054] Method 600 according to this disclosure is shown in Figure 6 The following discussion is conducted with reference to the figure. First, in step 610, an enhanced oil recovery (EOR) composition is introduced into a hydrocarbon-bearing formation. In one or more embodiments, the EOR composition is introduced into a subsurface region 510 of a target formation 550. The EOR nanofluid is as previously described. The hydrocarbon-bearing formation may include crude oil. In one or more embodiments, the hydrocarbon content of the hydrocarbon-bearing reservoir has been reduced by approximately one-third.

[0055] In method 600, step 620 includes displacing hydrocarbons in a hydrocarbon-bearing formation. The disclosed EOR composition can be used to displace the hydrocarbons. In one or more embodiments, the Janus carbon nanoparticles may have surfactant-like surface properties in the EOR composition. Therefore, the disclosed Janus carbon nanoparticles can be located at the downhole oil-water interface or rock-fluid interface, and thus can improve hydrocarbon mobility or alter the wettability of reservoir rocks, thereby increasing the degree of hydrocarbon displacement.

[0056] Step 630 in method 600 includes recovering the hydrocarbons. As described above, in the presence of the disclosed EOR composition, the hydrocarbons can have improved fluidity, thus increasing hydrocarbon recovery from the formation. Method 600 can achieve higher recovery of crude oil (OIIP) in original geological reserves.

[0057] The embodiments of this disclosure provide at least one of the following advantages. Using an alkaline solution is a simple and economically feasible method for functionalizing carbon microparticles. Compared to other functionalization methods, using the alkaline solution reduces the formation of excess liquid and gaseous waste.

[0058] Example

[0059] Example 1: Synthesis of carbon microparticles from waste plastics

[0060] In a typical synthesis, waste plastic water bottles (polymer PET) are cut into millimeter-sized pieces, and 10 grams of plastic fragments are placed in a crucible. After heating at 450°C for 60 minutes under a N2 atmosphere, the resulting carbon black powder is collected. The dry carbon powder is then broken down to micrometer-sized particles in a controlled manner by milling in a ball mill (Retsch IM 500 Nano) with 3 mm zirconium oxide beads at 35 Hz for 1 hour.

[0061] Example 2: Synthesis of carbon microparticles from waste coffee powder

[0062] In a typical synthesis, waste coffee powder is dried in an oven at 100°C under an air atmosphere, and then 10 grams of the dried coffee powder is transferred to a crucible. After heating at 450°C for 60 minutes under a nitrogen atmosphere, the resulting carbon black powder is collected. The dried carbon powder is then broken down to micron-sized particles in a controlled manner by grinding in a ball mill.

[0063] Example 3: Synthesis of carbon microparticles from lignin

[0064] In a typical synthesis, 10 grams of dry lignin powder is placed in a crucible and heated at 450°C for 60 minutes under a nitrogen atmosphere. The resulting carbon black powder is collected and then ground using a ball mill. Carbon particles with sizes in the micrometer range are obtained.

[0065] like Figure 9 As shown, the formation of the carbon structure in the above sample was confirmed by Raman spectroscopy, with its characteristic D band located at approximately 1365 cm⁻¹. -1 At this location, the G-zone is situated at approximately 1605 cm. -1 Place.

[0066] Example 4: Surface functionalization using alkaline solution

[0067] Two grams of carbon microparticles were placed in a beaker, and 50 mL of a 1 M potassium hydroxide (KOH) solution in a 1:1 water-ethanol mixture was added with magnetic stirring. The solution was sonicated using a probe-type sonicator (Fisher Scientific CL-18, 120 W, 25 kHz) with pauses for 15 minutes. The KOH-treated carbon microparticles were collected by filtration, dried in an oven at 100 °C under air atmosphere, and then transferred to a tube furnace and heated to 450 °C in air and N2 for 60 minutes. After cooling the sample to room temperature, the resulting functionalized carbon microparticles exhibited an enhanced hydrophilic surface and were readily dispersed in water.

[0068] Example 5: Formation of Janus carbon particles

[0069] Carbon nanoparticles were ground using a laboratory ball mill (Netzsch, MiniCer). First, 140 mL of zirconia beads (0.45 mm in diameter) were placed in the grinding chamber as the grinding media. Then, 10 g of micron-sized carbon powder was mixed with 200 mL of water in an open mixing vessel and pumped through the grinding chamber. The grinding speed was set to 3000 rpm, and the feed fluid was circulated in the grinding chamber at a rate of 100 mL / min. After grinding for 2 hours, the carbon nanoparticle fluid was collected, and the carbon nanoparticles were separated by centrifugation and washed with ethanol.

[0070] Figures 7 and 8 show photographs of examples of Janus carbon nanoparticles synthesized from lignin and waste coffee powder in a water-organic solvent mixture. Clearly, the carbon microparticles synthesized skeletally from lignin and waste coffee powder are hydrophobic and dispersed in the organic solvent (partial(a)) of Figures 7 and 8. After treatment with KOH, the carbon microparticles become hydrophilic and readily dispersed in the aqueous phase (partial(b)) of Figures 7 and 8. Upon grinding into nanoscale particles, the carbon nanoparticles exhibit typical Janus properties and tend to assemble at the water-organic solvent interface (partial(c)) of Figures 7 and 8.

[0071] The particle size and zeta potential of the generated carbon microparticles and Janus carbon nanoparticles in aqueous suspension were measured using a Brookhaven 90PLUS / PALS instrument via dynamic light scattering. The results are summarized in Table 1.

[0072] Table 1. Particle size and zeta potential of the synthesized carbon microparticles and Janus carbon nanoparticles

[0073]

[0074] After carbonization of waste plastics or biomass waste, carbon powder can be ground to micron-sized particles of several micrometers, with a very low surface charge density and a zeta potential of -8.5 mV to +3.7 mV. After surface functionalization at high temperature via KOH treatment, the negative surface charge density increases significantly to approximately -50 mV, while the particle size remains largely unchanged. After ball milling, the size of the resulting Janus carbon nanoparticles is reduced to submicron dimensions, and due to the formation of an asymmetric Janus nanostructure, the surface charge density decreases to approximately -20 mV to -32 mV.

[0075] Although only a few exemplary embodiments have been described in detail above, those skilled in the art will readily understand that many modifications can be made to the exemplary embodiments without substantially departing from the invention. Therefore, all such modifications are intended to be included within the scope of this disclosure as defined by the appended claims.

Claims

1. A method for preparing an enhanced oil recovery composition, comprising: Waste carbon materials are carbonized to provide carbon microparticles with hydrophobic surfaces; The carbon microparticles are functionalized with an alkaline solution so that the carbon microparticles include a hydrophilic surface; as well as The carbon microparticles are ground to provide carbon nanoparticles, wherein the carbon nanoparticles include the hydrophilic surface and the hydrophobic surface.

2. The method of claim 1 further comprises mixing the carbon nanoparticles with a water-based fluid to provide an enhanced oil production fluid.

3. The method according to claim 1 or 2, wherein, The waste carbon materials include waste plastic materials or biomass waste.

4. The method according to claim 3, wherein, The waste plastic materials include polymers selected from the group consisting of: polypropylene (PP), polystyrene (PS), acrylonitrile-butadiene-styrene (ABS), polyethylene terephthalate (PET), polyester (PES), polyamide (PA), polyvinyl chloride (PVC), polyurethane (PU), polycarbonate (PC), polyvinylidene chloride (PVDC), polyethylene (PE), and combinations thereof.

5. The method according to claim 3 or 4, wherein, The waste plastic material is waste plastic bottles.

6. The method according to claim 3, wherein, The biomass waste includes biomass waste selected from seaweed, algae, coffee, tea, fruit peels, nut shells, and combinations thereof.

7. The method according to claim 3 or 6, wherein, The biomass waste includes molecules selected from starch, chitin, lignin, cellulose, and combinations thereof.

8. The method according to any one of claims 1 to 7, wherein, Carbonizing the waste carbon material involves heating the waste carbon material at a temperature in the range of 300 to 550°C.

9. The method according to any one of claims 1 to 8, wherein, The carbon microparticles have an average particle size in the range of 5 to 500 μm.

10. The method according to any one of claims 1 to 9, wherein, Functionalizing the carbon microparticles with the alkaline solution includes sonicating the carbon microparticles in the alkaline solution for 1 to 15 minutes.

11. The method according to claim 10, wherein, Functionalizing the carbon microparticles with the alkaline solution further includes heating the carbon microparticles at a temperature in the range of 300 to 550°C after ultrasonic treatment.

12. The method according to any one of claims 1 to 11, wherein, The alkaline solution is a potassium hydroxide solution.

13. The method according to any one of claims 1 to 12, wherein, The alkaline solution has a concentration in the range of 1.0 to 4.0 M.

14. The method according to any one of claims 1 to 13, wherein, The hydrophilic surface functional group is a hydroxyl group.

15. The method according to any one of claims 1 to 14, wherein, Grinding the carbon microparticles involves ball milling the carbon microparticles at a speed of 2000 to 4000 rpm for 0.5 to 8 hours.

16. The method according to any one of claims 1 to 15, wherein, The carbon nanoparticles have an average particle size in the range of 10 to 2000 nm.

17. The method according to any one of claims 2 to 16, wherein, The water-based fluid is water, seawater, or salt water.

18. The method according to any one of claims 2 to 17, wherein, The water-based fluid includes one or more additives selected from the group consisting of surfactants, stabilizers, and combinations thereof.

19. An enhanced oil recovery method, comprising: The enhanced oil recovery composition according to claim 2 is introduced into hydrocarbon-bearing formations; Displace hydrocarbons from the hydrocarbon-bearing strata; as well as The hydrocarbons are recovered.

20. The method according to claim 19, wherein, The carbon nanoparticles are present in an amount ranging from 0.001 to 3.0% by weight.